Membrane Fc-IgG and C3b receptors on myeloid leukaemia cells: a comparison with cytoplasmic acid naphthyl acetate esterase cytochemistry. Issue 5 (May 1983) - Scott, C S; Bynoe, A G; Linch, D C; Allen, C; Hough, D; Roberts, B E
Abstract : Membrane receptors for IgG and C3b were examined on blast cells from 57 cases of acute myeloid leukaemia. These acute leukaemias were classified as myeloblastic, myelomonocytic or monocytic following morphological, cytochemical, and immunological investigations. The membrane receptors of leukaemic blast cells appear to be directly related to the degree of monocytic differentiation with the lowest receptor activities found in acute myeloblastic leukaemia. A comparison was also made between receptor and cytoplasmic acid naphthyl acetate esterase (ANAE) activities in 29 morphologically and immunologically-defined myelomonocytic and monocytic leukaemias. This study revealed that the receptor-positive "monocytic component" in a significant proportion of cases showed unexpectedly weak or negative ANAE reactions suggesting a more cautious approach to the interpretation of ANAE cytochemistry in acute leukaemias. The normal development of cytoplasmic ANAE and membrane receptors is also discussed and compared with their abnormal patterns of expression associated with leukaemic transformation.